The impact of rehabilitation and physical exercises using a number of assistive tools on certain physical attributes and the reduction of lower back pain in women - Saber, L.Dr. Awara Saber Hamad; Muhammed, Prof.Dr. Zana Muhammed Muhammed Saleh; Gamal, Asst.L. Ahmed Gamal Fath; Dilshad, Asst.L. Diman Dilshad Abdullah (Sulaimani Journal for Humanities, 2025)
- Preparing rehabilitation and physical exercises to treat lower back pain and improve the strength of the back muscles and flexibility of the spine. - Identifying the effect of rehabilitation and physical exercises using a number of assistive devices on some physical characteristics and relieving lower back pain in women. - Identifying the effect of rehabilitation and physical exercises using a number of tools to help improve the strength of the back muscles and the flexibility of the spine for women. The researchers used the experimental method (one group) in accordance with the nature of the problem, and the research sample included female patients at the Rheumatology and Physiotherapy Center_Koysinjaq City, the researchers used a set of therapeutic and physical exercises using means of assistance for a period of (6) weeks, with (24) treatment sessions on female patients aged (34-38) years, numbering (8). The researchers processed the data statistically using the statistical package (SPSS) version (28). The researchers reached a number of conclusions, including: Rehabilitation and physical exercises using a number of means of assistance had a positive effect in reducing lower back pain in women. Rehabilitation and physical exercises using a number of means of assistance had an effect in improving the flexibility of the spine in women, while one of the most important recommendations was the necessity of using rehabilitative and physical exercises due to their importance. In relieving lower back pain and improving the strength and flexibility of the back muscles, and the necessity of using means of assistance because of their positive effect in relieving lower back pain, it is necessary to rely in rehabilitation centers on rehabilitative and physical exercises in addition to physical treatments to help the injured person recover quickly and return to his normal condition as quickly as possible.
Keywords: Rehabilitation and physical exercises; assistive devices; lower back pain